P-355 Association between high serum uric acid level and adverse reproductive outcomes in infertile women with polycystic ovary syndrome. (30th June 2022) - Mu, L; Liu, C; Yang, H
Abstract: Study question: Does high serum uric acid (SUA) level affect the reproductive outcomes in women with polycystic ovary syndrome (PCOS) undergoing in-vitro fertilization (IVF)? Summary answer: Elevated SUA is associated with decreased live birth rate, biochemical pregnancy rate and clinical pregnancy rate, and increased miscarriage rate in women with PCOS. What is known already: SUA levelsand the prevalence of hyperuricemia (25.48%) are both significantly higher in women with PCOS than in women without PCOS (8.74%). SUA levels also can be used as a predictor of pregnancy complications (gestational diabetes mellitus and hypertensive disorders of pregnancy) and adverse foetal outcomes (preterm birth and low birth weight). Study design, size, duration: This retrospective cohort study was conducted ininfertile women with PCOS between September 2012 and December 2019. Participants/materials, setting, methods: A total of 1, 032 infertile PCOS women undergoing their first IVF/ICSI cycle were observed. Data of reproductive outcomes including live birth rate, biochemical pregnancy rate, clinical pregnancy rate, and miscarriage rate were analyzed according to the quartile groups of SUA levels. Main results and the role of chance: In quartiles of SUA levels, there was a significant decreasing trend in live birth rate from the lowest quartile (Q1: 34.5%) to the highest (Q4: 19.2%) ( P for trend <0.001). Notably, the miscarriage rate in Q4 was significantly higher than that in the other 3 quartiles (all P values < 0.05). From Q1 to Q4, the incidence of miscarriage dramatically increased from 15.5% to 31.0% ( P for trend <0.05). In addition, the biochemical pregnancy rate and clinical pregnancy rate decreased significantly from the lowest quartile to the highest ( P for trend <0.05). With the first quartile of uric acid as the reference group, the logistic regression analysis showed that in both unadjusted and adjusted models, elevated SUA level was associated with significantly lower probabilities of live birth, biochemical pregnancy, and clinical pregnancy, and a higher risk of miscarriage in a linear fashion (all P for trend < 0.05). Limitations, reasons for caution: This study is limited by its retrospective design. It was difficult to ensure consistency in clinical practice among the physicians. Wider implications of the findings: Our study suggeststhat clinical physicians need to pay close attention to PCOS women with high SUA levelsbefore IVF treatment. Prospective studies to determine an appropriate range of lower-SUA levels prior to treatment is necessary to support our findings. Trial registration number: not applicable